Changing dimensions of poverty in India: A study with special reference to Bihar - Bala, Madhu (Bihar Journal of Public Administration)
Major issue of poverty has been facing in creating accurate parameters and identifying the poor, particularly in a country like India. The political regimes have kept moderating the parameters from time to time, as result, poverty has been found reduced but number of poor has kept increasing. Under the influence of this dominant assumption, the present paper intends to examine the changing paradigms of poverty in India and its dimensions with special reference to Bihar. The analysis reflect that assessment of poverty in India has been done on the parameters fixed by governments, perhaps in accordance with the policy priories and exhibiting the success in reducing poverty in India in their respective ways. The parameters developed after independence were gradually moderated every time to show the reduction in poverty rate. But in post reforms period, the parameters of the poverty were brought closer to the minimum needs of the common masses, however, it is still far below meeting the minimum basic needs. The changed definition and international instruments have made Indian governments to define poverty in multidimensional parameters, particularly after introduction of food security law and issuance of UN SDGs. The UNDP$1 (Bs MPI has shown positive shift in poverty situation in India and Bihar. Reproduced s
Keywords: Poverty, measurement, Income/nutrition-based, Multidimensional, India, Bihar